1992
DOI: 10.1093/nar/20.20.5357
|View full text |Cite
|
Sign up to set email alerts
|

Group I permuted intron-exon (PIE) sequences self-splice to produce circular exons

Abstract: Circularly permuted group I intron precursor RNAs, containing end-to-end fused exons which interrupt halfintron sequences, were generated and tested for selfsplicing activity. An autocatalytic RNA can form when the primary order of essential intron sequence elements, splice sites, and exons are permuted in this manner. Covalent attachment of guanosine to the 5' half-intron product, and accurate exon ligation indicated that the mechanism and specmrcity of splicing were not altered. However, because the exons we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
101
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 29 publications
(22 reference statements)
4
101
0
1
Order By: Relevance
“…Theses investigations allowed us to permute the order of the intron and exon sequence without distorting the tertiary structure of the permuted intron architecture. Puttaraju & Been (1992) first reported that circular permutation of the group I intron from both the Anabena pretRNA intron and the Tetrahymena intron generated a circular RNA exon in vitro. Another PIE from the T4 phage group I intron was later shown to be applicable for generating the circular exon (Ford & Ares, 1994).…”
Section: Group I Intron Self-splicing and The Permuted Intron-exon (Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Theses investigations allowed us to permute the order of the intron and exon sequence without distorting the tertiary structure of the permuted intron architecture. Puttaraju & Been (1992) first reported that circular permutation of the group I intron from both the Anabena pretRNA intron and the Tetrahymena intron generated a circular RNA exon in vitro. Another PIE from the T4 phage group I intron was later shown to be applicable for generating the circular exon (Ford & Ares, 1994).…”
Section: Group I Intron Self-splicing and The Permuted Intron-exon (Pmentioning
confidence: 99%
“…As the exon sequence does not participate in the selfsplicing reaction, the exon sequence in the PIE sequence is replaced with another foreign sequence. Based on this concept, several circular RNAs have been developed by the PIE method, i.e., the tat-activated response (TAR) RNA (Puttaraju & Been, 1995;Bohjanen et al, 1996;Bohjanen et al, 1997), rev responsive element (Puttaraju & Been, 1995), HDV ribozyme (Puttaraju et al, 1993;, tRNA (Puttaraju & Been, 1992), Bacillus subtilis PRNA , mRNA encoding GFP (Perriman & Ares, 1998), yeast actin exon (Ford & Ares, 1994), hammerhead ribozyme (Ochi et al, 2009), and streptavidin RNA aptamer (Umekage & Kikuchi, 2006, 2009a, 2009b (Table 1). Fig.…”
Section: Group I Intron Self-splicing and The Permuted Intron-exon (Pmentioning
confidence: 99%
“…Finally, either Rne protein alone or purified degradosomes preferentially cleave monophosphorylated substrates 20 -30-fold more rapidly than their triphosphorylated counterparts (4). Together, these results imply that the vectorial nature of mRNA decay is a reflection of the inherent preference of Rne for 5Ј-monophosphorylated substrates.To address whether Rne or degradosomes display 5Ј-end dependence in vivo where a circular RNA would be exposed to all the components of the degradative machinery, I have constructed chimeric RNAs in which a portion of the rpsT mRNA is embedded in a permuted group I intron, a construction that should permit its precise, autocatalytic circularization (14,15). In this work I show that circular rpsT mRNAs form efficiently and are 4 -6-fold more stable than their linear counterparts.…”
mentioning
confidence: 99%
“…To address whether Rne or degradosomes display 5Ј-end dependence in vivo where a circular RNA would be exposed to all the components of the degradative machinery, I have constructed chimeric RNAs in which a portion of the rpsT mRNA is embedded in a permuted group I intron, a construction that should permit its precise, autocatalytic circularization (14,15). In this work I show that circular rpsT mRNAs form efficiently and are 4 -6-fold more stable than their linear counterparts.…”
mentioning
confidence: 99%
“…A circularly permuted group I intron precursor RNA consisting of end-to-end fused exons that interrupt half intron sequences, self-splices to generate a circular RNA. 81 As it was demonstrated later, foreign sequences can be integrated into the exon of such a permuted self-splicing system, thus allowing the synthesis of circRNAs with desired sequence elements. 82 Based on the permuted intron exon (PIE) method, a variety of circular RNAs up to the length of 1130 nts have been generated in vitro as well as in vivo, mostly in E.coli cells.…”
Section: Ribozymes For Rna Circularizationmentioning
confidence: 97%